2012
DOI: 10.26719/2012.18.4.393
|View full text |Cite
|
Sign up to set email alerts
|

393 Costs associated with tuberculosis diagnosis and treatment in Yemen for patients and public health services

Abstract: This study determined the costs associated with tuberculosis (TB) diagnosis and treatment for the public health services and patients in Sana'a, Yemen. Data were collected prospectively from 320 pulmonary and extrapulmonary TB patients (160 each) who were followed until completion of treatment. Direct medical and nonmedical costs and indirect costs were calculated. The proportionate cost to the patients for pulmonary TB and extrapulmonary TB was 76.1% and 89.4% respectively of the total for treatment. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
3
10
1
Order By: Relevance
“…These results are somewhat comparable to the findings of similar studies published elsewhere [10, 13]. However, a few studies from developing and developed countries showed that the cost of TB medicines ranged from 4.7–63.8% of the total cost of TB management [6, 9–11, 14, 32]. Differences in cost accounting methods, characteristics of study population and variability in the unit cost of TB medicines are some of the factors that could explain inconsistency in the findings of various studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results are somewhat comparable to the findings of similar studies published elsewhere [10, 13]. However, a few studies from developing and developed countries showed that the cost of TB medicines ranged from 4.7–63.8% of the total cost of TB management [6, 9–11, 14, 32]. Differences in cost accounting methods, characteristics of study population and variability in the unit cost of TB medicines are some of the factors that could explain inconsistency in the findings of various studies.…”
Section: Discussionsupporting
confidence: 89%
“…Among these out-of-pocket payments, transportation and special food costs created the highest impact. Consistent with our findings, studies from the Netherlands, Tajikistan, Yemen, India and Thailand reported higher transportation and special food costs [7, 12, 14, 22, 33]. As such, weekly packing of TB drugs in the presence of suitable treatment supporters could be an option to reduce the out-of-pocket costs to the patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Data extracted from eligible TB-related cost surveys comprised: survey country, year of data collection, survey setting, survey sample size, local currency unit exchange rate, methods used to estimate TB-related costs, and mean TB-related costs stratified into subcategories of direct, indirect, and total TB-related costs. In Brazil and Yemen, where articles reported mean TB-related costs for different patient subgroups (e.g., directly observed therapy versus self-administered therapy), an unweighted mean overall estimate was calculated across subgroups [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%